1997
DOI: 10.1002/(sici)1096-9861(19970915)386:1<60::aid-cne7>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Callosal neurons in the cingulate cortical plate and subplate of human fetuses

Abstract: Given the scarcity of data on the development of the cerebral cortex and its connections in man, four brains of human fetuses at 25, 26, 30, and 32 weeks postovulation were used to investigate the following: 1) the radial distribution of callosal neurons in the cingulate cortex at the immediate postmigratory period; 2) the existence of callosally projecting neurons in the cortical subplate; and 3) the dendritic morphology of developing callosal neurons. The carbocyanine dye (1,1'-dioctadecyl-3,3,3',3'-tetramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…3A) resembled closely those of callosally-projecting SP cells (lower row in Fig. 3B), previously described (deAzevedo et al 1997). Likewise, diaphorase-positive cells could be classified into four types, according to the alignment of their dendritic arbors in relation to the pia mater: radially-oriented ( Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…3A) resembled closely those of callosally-projecting SP cells (lower row in Fig. 3B), previously described (deAzevedo et al 1997). Likewise, diaphorase-positive cells could be classified into four types, according to the alignment of their dendritic arbors in relation to the pia mater: radially-oriented ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…In a previous work we have shown that by 25 wpo both SP and CP cingulate neurons already project through the corpus callosum (deAzevedo et al 1997). Thirty-five wpo is considered to mark the beginning of SP dissolution stage for the somatosensory cortex (Kostovic and Rakic 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Early synaptogenesis and a waiting compartment for thalamocortical afferents were demonstrated in the human cingulate cortex (Kostović & Krmpotić, 1976), the human auditory cortex (Krmpotić-Nemanić et al 1983), human and monkey prefrontal cortex (Kostović & Goldman-Rakic, 1983), human and monkey visual cortex (Kostović & Rakic, 1984), and human and monkey somatosensory and visual cortex (Kostović & Rakic, 1990). It was also demonstrated that the subplate in humans serves as a waiting compartment for basal forebrain cholinergic afferents (Kostović, 1986), and in rhesus monkeys for callosal and ipsilateral corticocortical afferents (Goldman- , which was later confirmed for human brain, too (DeAzevedo et al 1997). The subplate zone was also incorporated in the first revision of the original Boulder Committee (1970) scheme, as well as in its recent revision (Bystron et al 2008).…”
Section: Discovery Of the Subplate Zonementioning
confidence: 99%
“…Although the rapid differentiation of subplate neurons into five neuronal types between 17 and 25 PCW coincided with the ingrowth of thalamocortical (Kostovic & Goldman-Rakic 1983;Kostovic & Rakic 1984;Kostovic & Rakic, 1990), basal forebrain cholinergic (Kostović, 1986), and cortico-cortical afferent fibres (DeAzevedo et al 1997) into the subplate zone, subplate neurons continued with further dendritic growth even after these afferents had relocated to the cortical plate, up to the seventh postnatal month (Mrzljak et al 1988(Mrzljak et al , 1990(Mrzljak et al , 1992. Fusiform neurons with very long dendrites were the most frequently impregnated interstitial cell type in the gyral white matter after birth (Mrzljak et al 1990), but slightly modified pyramidal neurons and multipolar non-pyramidal interstitial neurons were also present (Kostovic & Rakic, 1980;Mrzljak et al 1990).…”
Section: Morphological Diversitymentioning
confidence: 99%